Restaurant color's as stimuli to enhance pleasure feeling and its effect on diners' behavioral intentions in the family chain restaurants - Othman, Mohhidin; Goodarzirad, Bahar (Penerbit Universiti Teknologi MARA (UiTM) Malaysia, 2013)
Colors have significant impact on our daily life and play an important role in enhancing an environment as well as forming impressions.Restaurants’ servicescape color has received limited research interest in the past but it is becoming an important consideration in future servicescape design and construction. The aim of this paper is to investigate the effects of servicescape color on diners’ pleasure feelings and behaviors in family chain restaurants in Malaysia. Data gathered through the convenience sampling of family chain restaurant customers using a structured self administrated questionnaire.This study found that color an aspect of servicescapes as stimuli that enhance pleasure feeling in consumption experience and in turn affected diners’ behavioral intentions.Findings show that colors play persuasive roles in forming feelings and behaviors, and restaurant managers should focus on the color of service scape as it plays an important role in creating positive consumer outcomes and building stronger customer relationships.